2008
DOI: 10.1007/s00134-008-1078-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a transcutaneous carbon dioxide monitor in severe obesity

Abstract: The accuracy of estimation of PaCO(2) by transcutaneous monitoring was generally good in comparison with standard arterial blood gases examination. The device appears to be promising for use in obese patients to evaluate abnormalities in their alveolar ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 13 publications
6
25
0
1
Order By: Relevance
“…Basing on the results of our study, we may speculate that local conditions at the site of sensor location, including the thickness and conductivity of the skin are more important for PtcO 2 and PtcCO 2 measurement than whole body composition (Kesten et al 1991). This is supported by the findings of other authors who demonstrated that even in morbidly obese patients PtcCO 2 monitoring is a reliable method and its results correlate with arterial blood gases (Soto et al 2014;Maniscalco et al 2008).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Basing on the results of our study, we may speculate that local conditions at the site of sensor location, including the thickness and conductivity of the skin are more important for PtcO 2 and PtcCO 2 measurement than whole body composition (Kesten et al 1991). This is supported by the findings of other authors who demonstrated that even in morbidly obese patients PtcCO 2 monitoring is a reliable method and its results correlate with arterial blood gases (Soto et al 2014;Maniscalco et al 2008).…”
Section: Discussionsupporting
confidence: 84%
“…However, some authors documented that transcutaneous gas tensions do not depend on body mass index (BMI) (Soto et al 2014;Maniscalco et al 2008;Janssens et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index, tissue hypoperfusion, and the use of vasoconstricting drugs may affect accuracy. 18,19,20 In line with the results of Maniscalco et al, 21 which found a good agreement between P aCO 2 and P tcCO 2 (bias 1.3 mm Hg and limits of agreement Ϫ4 to 1.1) in a study of severe obese subjects (body mass index 43.7 kg/m 2 ), we considered that the body mass index of our subjects (mean 34 kg/m 2 ) did not affect the accuracy of P tcCO 2 . On the other hand, only 2 hypotensive subjects were included.…”
Section: Discussionsupporting
confidence: 75%
“…Intra-individual analysis of the agreement between PtcCO 2 and PaCO 2 data pairs collected after extubation of the two patients showed no considerable differences to the patients whose lungs were ventilated. These findings are supported by a study most recently published by Maniscalco and colleagues [22] and performed in severely obese and clinically unstable patients using the TOSCA device (Linde Medical Sensors AG, Basel, Switzerland). These authors reported good agreement of PtcCO 2 and PaCO 2 in both spontaneously breathing and ventilated patients.…”
Section: Discussionsupporting
confidence: 79%